Investigacion de frijol en campos de agricultores en el CIPA-V- Ancash- Peru - Antezana, A. (International Center for Tropical Agriculture, 1987)
In coastal Ancash, Peru, on-farm studies were conducted on fertilization (0-0-0 and 40-60-0 kg/ha NPK), density (90,000 and 120,000 plants/ha), and weed control (2 and 3 manual weedings, resp.) to determine their effect on yields of beans in monoculture. Significant differences among treatments were found as well as a relationship between fertility and density. Weed control was not effective. Treatments with the highest density and fertilization levels were the most profitable. (CIAT)